Analisis Usaha Penangkapan Dengan Alat Tangkap Jaring Dasar (Bottom Gill Net) di Kelurahan Sosor Gadong Kecamatan Sosor Gadong Kabupaten Tapanuli Tengah - Grasia A Simamora; Hendrik; Tince Sofyani (JURNAL SOSIAL EKONOMI PESISIR, 2020)
This study was aimed to determine the level of investment, to analyze production and income, and to analyze how the business analysis of fishing with bottom gill net. The method used is a survey method with 30 respondents as the ship's owner and sample survey. The results showed that the total investment for a business of bottom gill net with a motorboat was IDR.70.526.770 and motor boats in the amount of IDR. 21.580.905. As for the annual motorboat income from IDR. 57.919.935 per year and motor boats in the amount of IDR. 13.417.187 per year. The criteria for investing in a base power business with a motorboat have shown a Revenue Cost of Ratio (RCR) of 1.47 and a motorboat of 1.43 that RCR > 1 and the gill net business is viable and feasible to continue. While the FRR is 83.35% for motorboat fishermen and 65.92% for motorboats, it is above the Bank's current interest rate of 6.3% / year, making the investment worthwhile. The payback period (PPC) for motorboats is 1.24 and for motor boats 1.56.